1954
DOI: 10.1139/p54-084
|View full text |Cite
|
Sign up to set email alerts
|

IONIZATION PROBABILITY CURVES USING AN ELECTRON SELECTOR: RESULTS ON N2+, N+, Xe++

Abstract: An apparatus consisting of an electron energy selector built into a mass spectrometer is described. With it, initial ionization yield curves may be obtained. The interpretation of these curves is discussed, and the following new measurements reported:[Formula: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
2
1

Year Published

1958
1958
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(17 citation statements)
references
References 8 publications
6
8
2
1
Order By: Relevance
“…The electrostatic parallel-plate electron-energy selector (34, 35) was simple in design, but Helmholz coils were necessary to shield out stray magnetic fields. A 127" cylindrical electrostatic deflector (36)(37)(38) was one of the more popular early electron monochromator designs, because the foci of electron trajectories are located at the field boundaries. With this device, electron beams of A with energy bandwidths < 0.1 eV and energy range of 0-50 eV became available (37).…”
Section: A Designsmentioning
confidence: 99%
“…The electrostatic parallel-plate electron-energy selector (34, 35) was simple in design, but Helmholz coils were necessary to shield out stray magnetic fields. A 127" cylindrical electrostatic deflector (36)(37)(38) was one of the more popular early electron monochromator designs, because the foci of electron trajectories are located at the field boundaries. With this device, electron beams of A with energy bandwidths < 0.1 eV and energy range of 0-50 eV became available (37).…”
Section: A Designsmentioning
confidence: 99%
“…Evidence for this comes from the discontinuities observed in the N + ionization efficiency curve within a few volts of threshold, (Clarke 1954, Burns 1955, Frost and McDowell 1956 and Kresling 1967, Kieffer andVan Brunt 1967). The poor agreement as to the position of the discontinuities and hence the corresponding dissociation limits suggests that the situation is more complicated that any single experiment indicates.…”
Section: Angular Distributions Of N + Ionsmentioning
confidence: 99%
“…Previous more detailed studies have suggested that breaks occur in the curve at -16.7 eV and -18.75 eV corresponding to the production of ions from the ~'l7" and B~C: states of N l . (Frost and McDowell 1955, Clarke 1954, Fox 1961, Kaneko 1961, Winters et a1 1966, Peresse et a1 1967, Hierl and Franklin 1967. There are also a number of reports ofstructure in the curve associated with autoionization (see Carbonneau and Marmet, 1973 and references therein).…”
Section: Cross Sections For the Production Of Ni N + And N + + Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 M EASUREMENTS of the appearance potentials of negative ions in the mass spectroscop~c a~~lysis of molecules are handicapped by the unavaIlabllIty of convenient and accurate standards for calibrating the effective energy of the electrons in the ion source. 7 M EASUREMENTS of the appearance potentials of negative ions in the mass spectroscop~c a~~lysis of molecules are handicapped by the unavaIlabllIty of convenient and accurate standards for calibrating the effective energy of the electrons in the ion source.…”
mentioning
confidence: 99%